Implementation of risk management in the medical device industry - Dumbrique, Rachelo (ProQuest LLC, 2011)
This study looks at the implementation and effectiveness of risk management (RM) activities in the medical device industry. An online survey was distributed to medical device professionals who were asked to identify RM-related activities performed during the device life cycle. RM activities and techniques included Establishing Risk Acceptance Criteria, Hazard Identification, Human Factors/Usability, Fault Tree Analysis (FTA), Design Failure Mode and Effects Analysis (DFMEA), Process Failure Mode and Effects Analysis (PFMEA), Hazard and Operability Study (HAZOP), Hazard Analysis and Critical Control Point (HACCP), Risk Benefit Analysis, and Risk Assessment of Customer Complaint. Devices were identified by type (therapeutic, surgical/clinical tools, diagnostic, instrument disposable, implantable, etc.), development history (new, second, third or later generation device), and time since market release. Respondents were also asked to indicate the degree of change made to the device as a result of RM activities and to rate the effectiveness of associated RM activities for the device. Survey results indicated that RM's impact and level of effectiveness on a medical device are dependent primarily on the device type and life-cycle stage (i.e., pre-market versus post-market). There is also some impact of development history and the time since the device was released to market.